2004
DOI: 10.1371/journal.pbio.0020398
|View full text |Cite
|
Sign up to set email alerts
|

Conservation and Evolution of Cis-Regulatory Systems in Ascomycete Fungi

Abstract: Relatively little is known about the mechanisms through which gene expression regulation evolves. To investigate this, we systematically explored the conservation of regulatory networks in fungi by examining the cis-regulatory elements that govern the expression of coregulated genes. We first identified groups of coregulated Saccharomyces cerevisiae genes enriched for genes with known upstream or downstream cis-regulatory sequences. Reasoning that many of these gene groups are coregulated in related species as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
208
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(231 citation statements)
references
References 124 publications
(167 reference statements)
22
208
0
1
Order By: Relevance
“…However, transcriptional profiling of the amino-acid starvation response in Neurospora crassa suggested that in these cells AA biosynthesis genes and tRNA-aminoacyl-transferases are highly co-regulated [44 ] and a meta-analysis of expression co-regulation between S. cerevisiae and C. albicans identified distinctions in the mode of tRNA-aminoacyl-transferases co-regulation between the two species [4]. Consistently, phylogenetic analyses of the Gcn4 element (TGASTCA) enrichment showed that it is conserved in the amino-acid biosynthesis regulon in most ascomycetes and that it is found upstream of genes encoding tRNA-aminoacyltransferases in many species but excluded from the S. cerevisiae branch (Figure 1c) [16,44] ( Figure 1). …”
Section: Amino-acid Biosynthesissupporting
confidence: 59%
See 2 more Smart Citations
“…However, transcriptional profiling of the amino-acid starvation response in Neurospora crassa suggested that in these cells AA biosynthesis genes and tRNA-aminoacyl-transferases are highly co-regulated [44 ] and a meta-analysis of expression co-regulation between S. cerevisiae and C. albicans identified distinctions in the mode of tRNA-aminoacyl-transferases co-regulation between the two species [4]. Consistently, phylogenetic analyses of the Gcn4 element (TGASTCA) enrichment showed that it is conserved in the amino-acid biosynthesis regulon in most ascomycetes and that it is found upstream of genes encoding tRNA-aminoacyltransferases in many species but excluded from the S. cerevisiae branch (Figure 1c) [16,44] ( Figure 1). …”
Section: Amino-acid Biosynthesissupporting
confidence: 59%
“…It is thus becoming apparent that the level of plasticity of these networks during evolution is very high. In addition to these spectacular rearrangements of metabolic regulators, other studies provide support for massive rearrangements of the proteasome regulatory network and subtler rewirings of cell cycle regulatory circuits [16,55]. Surprisingly, large-scale modifications in transcriptional regulatory network connections occur in the control of pathways and complexes essential for cellular growth like the ribosomal and glycolytic regulons, while other apparently less constrained pathways are conserved [55].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…start sites, is correlated with the chromatin structure 34 . In the human genome, synonymous substitution rate at non-CpG sites is the highest in regions of the open chromatin 35 , linking cis effects with chromatin structure. On the other hand, trans expression variability is largely affected by chromatin factors, which have more important roles in creating regulatory variation than transcription factors 36 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Drosophila, the Pumilio protein binds proteins involved in embryo patterning, whereas the S. cerevisiae homologue, Puf3, binds nuclear-encoded mitochondrial transcripts (22). When cis elements were compared among ascomycete fungi, PUF elements were found to be conserved, but the functional classes of genes in which they were found diverged substantially (9). The enrichment of nuclear-encoded mitochondrial transcripts containing Puf3 elements in fungi is lost along with fermentative capacity, suggesting that the function of the Puf3 cis-trans module has evolved while the structure remains unaltered (14).…”
mentioning
confidence: 99%